Green Synthesis of Spirooxindole-pyrrolidine/Piperidine Fused Nitrochromane: One Pot Three Component Stereo and Regioselective Cycloaddition - Nayak, Sabita; K. Mishra, Sambita; Bhakta, Sujitlal; Panda, Pravati; Baral, Nilofar; Mohapatra, Seetaram; S. Purohit, Chandra; Satha, Pardhasaradhi (Letters in Organic Chemistry, 2016)
Background: Now a day’s green synthesis for multicomponent reactions is a powerful tool for construction of five membered/six membered heterocyclic ring systems. The synthesis of regio and stereoselective complex architectural motifs following 1,3-dipolar cycloaddition reactions via ecofriendly methods are well reported. The synthesis of pyrrolidine/piperidine based heterocycles has been the center of attraction because of their pronounced biological activities. Methods: The present methodology deals with one pot three component cycloaddition reaction of isatin based azomethine ylide and substituted nitrochromene to synthesize new spirooxindole-pyrrolidine/piperidine fused nitrochromanes in refluxing ethanol within 2 hr. Results: A series of new spirooxindole-pyrrolidine/piperidine fused nitrochromanes were synthesized in good to excellent yield (78-89%) via one pot three component cycloaddition reactions. The obtained products were isolated in good yield by simple filtration. All the synthesized compounds were well characterized (1H, 13C, Mass and M.P). The regio/ stereochemical results were ascertained by X-ray crystallographic study. Conclusion: We have developed an ecofriendly method to synthesize twelve new and novel spirooxindolepyrrolidine/ piperidine fused nitrochromanes via one pot three component 1,3-dipolar cycloaddition reaction in nontoxic solvent in a shorter time. It offers several advantages such as regio/stereoselective synthesis of spirooxindolepyrrolidine/ piperidine fused nitrochromanes, shorter reaction time, mild reaction conditions, simple and environmentally friendly operational procedure.
Keywords: Isatin